HUBUNGAN PERILAKU MEROKOK DENGAN HASIL PEMERIKSAAN MIKROSKOPIS BAKTERI TAHAN ASAM DI RSU MAGUAN HUSADA WONOGIRI - Vector Stephen Dewangga; Rizky Fadzillah Sungka (Journal of Nursing and Health, 2024)
Tuberculosis (TB) is an infectious disease caused by the bacterium Mycobacterium tuberculosis that can affect the lungs and other organs. Indonesia has the second highest case of pulmonary TB in the world after India. Tuberculosis cases in the Wonogiri Regency area in 2020 amounted to 2,062 patients. There are several groups of people who have a higher risk of developing TB disease, one of which is smokers. Indonesia is the third largest cigarette consumer in the world. The purpose of this study was to determine the relationship between smoking behavior and the results of microscopic examination of Acid Resistant Bacteria at Maguan Husada Wonogiri General Hospital. This research method is an observational analytic study with a cross sectional design. The sample in this study amounted to 43 respondents obtained using purposive sampling technique. The study was conducted using sputum samples with the Ziehl Neelsen staining method. The statistical test used was Chi Square. The results of the Chi Square test obtained a value of p = 0.045 can be concluded that there is a relationship between smoking behavior and the results of microscopic examination of Acid Resistant Bacteria at Maguan Husada Wonogiri General Hospital.